2019
DOI: 10.1186/s40164-019-0145-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of some members of chemokine/cytokine network in the pathogenesis of thalassemia and sickle cell hemoglobinopathies: a mini review

Abstract: The word of hemoglobinopathy is described for an array of disorders that affecting hemoglobin (Hb) functions. Hb is a molecule with 68 kDa molecular weight, serving as oxygen carrying metalloprotein. Hemoglobinopathy includes a wide range of Hb structural deficits varying from thalassemia to sickle cell disease. Cyto-chemokine network members are pivotally involved in the pathogenesis of hemoglobinopathies, however, the exact role of these mediators in the development of these disorders yet to be well addresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…This activation is achieved by the PlGF-VEGFR-1 interaction and involves the PI-3 kinase/AKT and ERK-1/2 signaling pathways ( 335 ). Because VOC in SCD is promoted by inflammation and leukocyte adhesion stimulated by cytokines ( 197 , 336 , 337 ), antibody neutralization of PlGF was tried successfully for reduction of inflammation and vaso-occlusive complications in murine SCD models ( 317 ). Regulation of PlGF levels could also be achieved by manipulating factors that control its transcriptional or translational expression.…”
Section: Hemolysis Plgf and Complications Of Sickle Cell Diseasementioning
confidence: 99%
“…This activation is achieved by the PlGF-VEGFR-1 interaction and involves the PI-3 kinase/AKT and ERK-1/2 signaling pathways ( 335 ). Because VOC in SCD is promoted by inflammation and leukocyte adhesion stimulated by cytokines ( 197 , 336 , 337 ), antibody neutralization of PlGF was tried successfully for reduction of inflammation and vaso-occlusive complications in murine SCD models ( 317 ). Regulation of PlGF levels could also be achieved by manipulating factors that control its transcriptional or translational expression.…”
Section: Hemolysis Plgf and Complications Of Sickle Cell Diseasementioning
confidence: 99%
“…The CXCL12 signaling pathway plays a key role within cross-talk of the leukemic cells and BM microenvironment interactions. 7,16 To perform its activities, CXCL12 attaches to two namely receptors, CXCR4 and CXCR7 and further transduces on the mTOR pathway in pancreatic and gastric cancers, T cell leukemia, and the human renal cancer cells. Additionally, as described earlier in the text, chemokines are a superfamily of chemoattractant proteins that induce cytoskeletal rearrangement for firm adhesion to specific cells and directional migration.…”
Section: Downstream Signaling Pathways Activated By Cxcl12/cxcr4 7 Imentioning
confidence: 99%
“…Hence, this is of particular relevance to consider that chemokine receptors are extensively expressed by several normal as well as malignant non-leukocyte cell types. [3][4][5][6][7][8] Despite the sensitivity to chemotherapy, the long-term disease-free survival in AML sufferers remained low and it was reported that the majority of the patients most often enter the relapse phase from minimal residual disease (MRD). 9 BM is one of the main locations for MRD where the adhesion of AML cells to the BM components may provide protection from the chemotherapy reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Thalassaemia is caused by inherited autosomal recessive abnormalities in haemoglobin synthesis [1]. These abnormalities result in an imbalanced production of whole alpha‐ or beta‐globin chains, leading to the formation of defective haemoglobin molecules in both alpha‐ and beta‐thalassaemia, respectively [2]. Depending on the clinical severity and haemoglobin levels, thalassaemia patients may require regular packed red blood cell transfusions with iron chelation therapy, splenectomy or bone marrow transplantation in selected cases.…”
Section: Introductionmentioning
confidence: 99%